Do soundscape indices predict landscape‐scale restoration outcomes? A comparative study of restored seabird island soundscapes. Issue 1 (9th September 2019) - Borker, Abraham L.; Buxton, Rachel T.; Jones, Ian L.; Major, Heather L.; Williams, Jeffrey C.; Tershy, Bernie R.; Croll, Donald A.
Abstract : Measuring restoration outcomes is essential, but challenging and expensive, particularly on remote islands. Acoustic recording increases the scale of monitoring inexpensively; however, extracting biological information from large volumes of recordings remains challenging. Soundscape approaches, characterizing communities using acoustic indices, rapidly analyze large acoustic datasets and can be used to compare restoration sites against reference conditions. We tested this approach to measure nocturnal seabird recovery following invasive predator removal in the Aleutian Islands. We used recordings of nocturnal seabird soundscapes from six islands with varied histories of predators, from never invaded (one island) to 9–34 years post‐predator removal (four islands) and currently invaded (one island). We calculated 10 indices of acoustic intensity and complexity, and two pairwise indices of acoustic differences. Three indices reflected patterns of seabird recovery. Acoustic richness (measuring temporal entropy and amplitude) increased with time since predator removal and presence of historical predator refugia ( r 2  = 0.44). These factors and moonlight accounted for 30% of variation in cumulative spectral difference from the reference island. Over 10% of acoustic richness and temporal entropy was explained by Leach's Storm‐petrel ( Oceanodroma leucorhoa ) calls. However, indices characterized the soundscape of rat‐invaded Kiska Island like a never invaded island, likely due to high abiotic noise and few seabird calls. Soundscape indices have potential to monitor outcomes of seabird restoration quickly and cheaply, if confounding factors are considered and controlled in experimental design. We suggest soundscape indices become part of the expanding acoustic monitoring toolbox to cost‐effectively measure restoration outcomes at scale and in remote areas.